The Legal and Ethical Environment of Business - Lau, Terence; Johnson, Lisa (Open textbook library., 2011)
Terence Lau & Lisa Johnson's The Legal and Ethical Environment of Business is a book for today's student, who expects learning to be comprised not only of substance, but also of interactive exercises and multimedia. This book streamlines the presentation of material to ensure that every page is relevant, engaging, and interesting to undergraduate business students, without losing the depth of coverage that they need to be successful in their academic journeys and in their professional careers. This is not Legal Environment of Business (LEB) ”light.“ Rather, this is LEB without risk of students' eyes glazing over in boredom or from lack of comprehension. This is LEB presented in an exciting way, where every page is interesting to students and relevant to real life. The authors recognize that the sheer volume of information to be covered in a LEB course makes it one of the more challenging courses for the business undergraduate. Not only do typical LEB texts read like the first year curriculum at law school, but also the LEB course is grounded in the humanities, which can make the subject even more demanding for students who are also taking statistics, economics, finance, and accounting. Each chapter contains not only substantive law, but also illustrative videos, interactive exercises for hands-on learning, and discussion questions for critical thought. Additionally, each chapter presents ”A Question of Ethics“ section, which contains real world ethical dilemmas relevant to the topic under study. These videos, exercises, discussion questions, and ethics sections all provide opportunities for students to apply concepts that they are learning in the context of relevant LEB topics that shape or restrain actual decision-makers' actions. It's real world practice in the safety of the classroom environment. Lau & Johnson's The Legal and Ethical Environment of Business is a textbook that students will enjoy reading. This will encourage them to come to class prepared, and free you to teach the kind of course you want to teach. Request a desk copy and see for yourself.